MARKETING STRATEGY OF OMAH MBUDUR TOURISM DESTINATION IN WANUREJO VILLAGE, BOROBUDUR DISTRICT - Amilla, Agustin Kinthan; Pranoto, Pranoto; Dwijaningtyas, Srinata (International Journal Mathla’ul Anwar of Halal Issues, 2023)
The tourism sector is a profitable industrial sector for now, tourism involves many people and can revive various business fields so that it can become a global industry. Along with the development of information technology and transportation, this has become a trigger for the increase in new tourism products. Each tourism product needs to have its own characteristics so that it can compete with other tourism products.  The purpose of this study was to find out the existing tourism products in the Omah Mbudur Tourism Destination, to find out the existing management system in the Omah Mbudur Tourism Destination, and to find out the marketing strategy used by the management.  While the method used in research is descriptive qualitative. The results of this study indicate that Omah Mbudur is a destination with a village tourism concept that carries the theme of cultural arts related to basic human needs, namely clothing, food and boards along with activities such as VW safaris, jeep adventures, regional arts and so on. The management of the Omah Mbudur tourist destination is a mutual cooperation system, namely by entrusting the staff to their respective fields with the aim of characterizing the culture of the community.